Students' Cognitive, Affective, Behavioural and Social Engagement in Collaborative Writing - Addinna, Ainul; Ovilia, Ririn; Solusia, Carbiriena; Ramadhani, Syafitri (Jurnal Bahasa dan Sastra, 2024)
One of the effective strategies to improve writing skills is Collaborative Writing (CW). In the CW process, group members will engage and interact in the process of writing a text. Hence, student engagement becomes an important point that needs to be studied. Based on the EWT (Engagement with the Task) model from Philip and Duchesne, there are 4 dimensions of student engagement, namely cognitive, affective, attitudinal and social engagement. This research aims to analyze students' cognitive, affective, behavioral and social engagement in learning academic writing using collaborative writing method. Based on this objective, the appropriate research design is qualitative research using observation as a data collection technique and the instruments used are observation sheets and field notes supported by video recording during the learning process. From the results of the analysis conducted, it was found that during Collaborative Writing with peers the majority of participants in this study were involved cognitively, affectively and attitudinally.  In terms of social engagement, the patterns of all pairs were collaborative and expert/novice relationship